The Analysis Of Marketing Mix Strategy Of Wood Processing In Increasing The Salling Margin - Bunyamin Bunyamin; Sultan Iskandar (Green Publisher Indonesia, 2021)
The purpose of this study is to analyze whether the application of the marketing mix strategy through the SWOT formulation can increase the sales volume of processed wood. This research was conducted at the office of PT. Three